2018
DOI: 10.1128/aem.01680-18
|View full text |Cite
|
Sign up to set email alerts
|

A Vegetable Fermentation Facility Hosts Distinct Microbiomes Reflecting the Production Environment

Abstract: Fermented vegetables are highly popular internationally in part due to their enhanced nutritional properties, cultural history, and desirable sensorial properties. In some instances, fermented foods provide a rich source of the beneficial microbial communities that could promote gastrointestinal health. The indigenous microbiota that colonize fermentation facilities may impact food quality, food safety, and spoilage risks and maintain the nutritive value of the product. Here, microbiomes within sauerkraut prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Culture-dependent methods remain the gold standard for the strain-level characterization of fermentation microbiota; however, these methods are increasingly complemented by holistic, meta-omics methods (metagenomics, metatranscriptomics, metaproteomics and metabolomics) 55 . Molecular approaches have shown that fermented foods are frequently dependent on complex, multi-kingdom, microbial communities functioning in concert via dynamic succession processes [56][57][58][59] . However, despite this complexity, the presence of a so-called core microbiota (defined as widespread microorganisms that are central to the functions of these ecosystems) are often apparent in a wide range of fermented foods [60][61][62][63][64] .…”
Section: Making Fermented Foods Which Microorganisms Are Needed To Mamentioning
confidence: 99%
“…Culture-dependent methods remain the gold standard for the strain-level characterization of fermentation microbiota; however, these methods are increasingly complemented by holistic, meta-omics methods (metagenomics, metatranscriptomics, metaproteomics and metabolomics) 55 . Molecular approaches have shown that fermented foods are frequently dependent on complex, multi-kingdom, microbial communities functioning in concert via dynamic succession processes [56][57][58][59] . However, despite this complexity, the presence of a so-called core microbiota (defined as widespread microorganisms that are central to the functions of these ecosystems) are often apparent in a wide range of fermented foods [60][61][62][63][64] .…”
Section: Making Fermented Foods Which Microorganisms Are Needed To Mamentioning
confidence: 99%
“…Culture-based studies from the 1960s noted that LAB are in low abundance on the surfaces of cucumbers, beets, carrots, and other vegetables (67). A recent survey of a fermentation production facility found that LAB are in low levels in the green cabbage phyllosphere (49). Collectively, these studies demonstrate a consistently low abundance of LAB across other species and varieties of cabbage, as well as other vegetables.…”
Section: Discussionmentioning
confidence: 92%
“…Sequence-based data on cabbage phyllosphere bacterial diversity are very limited (43,49), and our amplicon sequence data help fill this gap. Across the three sites, Proteobacteria dominated the amplicon sequence data sets, with Bacteroidetes, Firmicutes (non-LAB), and Actinobacteria making up smaller fractions of the NCP at each site (Fig.…”
Section: Figmentioning
confidence: 99%
“…Many other food products, such as salami, sauerkraut, sourdough, surströmming and hákarl, wine, cheese, yoghurt and kefir, all rely on microbiomes for flavour, odour, texture and even shelf life. In vegetable fermentation facilities that produce spontaneously fermented sauerkraut, the raw vegetables and indoor environment and surfaces hosted distinct microbiomes, which were reflected in the final product (Einson et al , 2018). In contrast, human contamination was found to have no effect on the final product.…”
Section: The Concept and Mechanisms Of Stochasticity In Microbial Ecomentioning
confidence: 99%